The Birth of Energy Fossil fuels, thermodynamics and the politics of work - Daggett, Cara New (Duke University Press, 2019)
In The Birth of Energy Cara New Daggett traces the genealogy of contemporary notions of energy back to the nineteenth-century science of thermodynamics to challenge the underlying logic that informs today's uses of energy. These early resource-based concepts of power first emerged during the Industrial Revolution and were tightly bound to Western capitalist domination and the politics of industrialized work. As Daggett shows, thermodynamics was deployed as an imperial science to govern fossil fuel use, labor, and colonial expansion, in part through a hierarchical ordering of humans and nonhumans. By systematically excavating the historical connection between energy and work, Daggett argues that only by transforming the politics of work-most notably, the veneration of waged work-will we be able to confront the Anthropocene's energy problem. Substituting one source of energy for another will not ensure a habitable planet; rather, the concepts of energy and work themselves must be decoupled.